Transcriptomic signatures of neonatal acute respiratory distress syndrome in a prospective cohort of respiratory distress - Chan Liu; Qing Ai; Jingli Yang; Ying Fan; Wen Jia; Leyu Si; Yuting Yao; Feifan Chen; Shiyue Liu; Yu He; Yuan Shi (iScience)
Summary: Neonatal acute respiratory distress syndrome (NARDS) is challenging to differentiate from other respiratory conditions, and gestational age (GA) may influence gene expression. This study characterized whole blood transcriptomic profiles of NARDS in a pilot cohort of 48 neonates with respiratory distress, demonstrating a significant GA-dependent modulation of gene expression. Functional analyses revealed prominent involvement of interferon-related pathways in NARDS, with greater suppression in neonates born before 34 weeks. Immune cell infiltration was observed in term or late preterm neonates but was absent in more preterm cases. Machine learning identified three key predictive genes, among which ALOX15 and PTGDR2 were validated in an independent cohort, with area under the curve ranging from 0.68 to 0.83 across different GAs. The gene changes were also confirmed in a neonatal lipopolysaccharide-induced lung injury mouse model. These findings highlight the potential predictive and therapeutic value of ALOX15 and PTGDR2 for NARDS.